The Psychometric Properties of the Chinese Version of the Beck Depression Inventory-II With Middle School Teachers - Wang, Xiuna; Wang, Yutong; Xin, Tao (Frontiers in Psychology, 2020)
As previous researchers have found like other parts of the world, depression is prevalent among middle school teachers in China. The Beck Depression Inventory-II (BDI-II) has been widely used to detect depression among workers in different careers all over the world and has shown good scale properties but inconsistent factor structures. To examine the psychometric properties of the BDI-II among middle school teachers, a nationally representative sample of 4672 valid cases from 688 middle schools were included. We first generated a new bifactor model based on exploratory factor analysis and agglomerate cluster analysis of the residual item correlations, then validated the modes and examined measurement invariance across gender and school location with multiple-group CFA. Results indicated that (1) a new bifactor model with a general factor and two group factors (cognitive-affective group factor and somatic group factor) fitted well to the data (WLSMV χ2 = 745.651, df = 173, p < 0.001, CFI = 0.983, TLI = 0.979, RMSEA = 0.037 (90% CI [0.035 0.040]), Omega values for the three factors varied from 0.88 to 0.92; (2) measurement invariance tests indicated the BDI-II could equally measure depression of middle school teachers across gender and school location groups. All the findings suggest that the BDI-II is a self-report inventory with good psychometric properties for measuring depression among middle school teachers in China.